A Historical Overview of Art and Music-Based Activities in Social Work with Groups: Nondeliberative Practice and Engaging Young People's Strengths. Issue 3 (3rd July 2017) - Kelly, Brian L.; Doherty, Lauren
ABSTRACT: This article provides a historical overview of the use of art and music-based activities in social work with groups. The authors review archival, empirical, and theoretical literature that explores the use and effectiveness of these activities in the recreation movement and group work practice from the late 19th to mid-20th centuries, the Hull House settlement in Chicago from the late 19th to mid-20th centuries, and in recent group practice in social work and related fields. Findings suggest that art and music-based activities encourage and facilitate nondeliberative practice and allow for important opportunities to engage young people's strengths.